Planar vortices in a Lorentz symmetry breaking environment - E. Mavigno; H. Belich; G. Luchini (European Physical Journal C: Particles and Fields)
Abstract We revisit planar vortex solutions within a model derived from the dimensional reduction of scalar electromagnetism, with a quartic potential incorporating the Carroll–Field–Jackiw term. We explore analytically and numerically the influence of a Lorentz symmetry-breaking constant field on these configurations and our analysis shows how this constant field can produce a new asymptotic behaviour characterised by damped oscillations of the electric and magnetic fields on the edge of the vortices.